Developing a healing and wellness program for First Nations boys and men: The Mishoomsinaang Mentorship Program - George, Julie; Ninomiya, Melody Morton; Graham, Kathryn; Wells, Samantha (Te Rau Ora, 2021)
Very little is known about men’s lived experiences with, or tangible barriers to, accessing or receiving support for mental health, substance use, and violence challenges. This paper describes the development of a healing and wellness program for boys and men, developed by men in a First Nation community in southern Ontario, Canada, drawing on local data collected and using participatory action research. Men’s mental wellness was identified as a priority area after reviewing preliminary research findings from a community-wide survey; interviews with people with lived experiences with mental health, substance use, and/or violence challenges; and focus groups with service providers. Photovoice was then used as a form of participatory action research to develop a) a knowledge base on men’s health and well-being across the life course and b) a comprehensive, integrated, and culturally appropriate program of services for boys and men. Men who participated in the Photovoice study developed a program that supports Mino Bimaadiziwin, a way of life lived in accordance with original cultural teachings on the importance of Spiritual connectedness and how to live as Spiritual beings in harmony with all of Creation. We share how this community-driven research led to scalable program and recommendations to improve Indigenous boys and men’s mental health and wellness.